Kajian Studi Pelaksanaan Standar Operasional Prosedur Pemasangan Infus Dan Gambaran Faktor Yang Mempengaruhi Kejadian Phlebitis Di Ruang Amarilis Paviliun Abiyasa Geriatri RSUD Prof. Dr. Margono Soekardjo Purwokerto - Mila Dian Nur; Indri Heri (Borneo Nursing Journal (BNJ), 2025)
Improper installation of intravenous catheters is one of the factors causing phlebitis, therefore officers must pay attention to the type, size, installation location and duration of intravenous catheter installation. The purpose of this study review is to observe nurse compliance in the implementation of standard operating procedures for intravenous catheter insertion and describe the factors that influence the incidence of phlebitis in the inpatient room of Amarilis room, Prof. Dr. Margono Soekarjo Purwokerto Hospital. This study review was conducted by observing 10 nurses and observing factors that influence the incidence of phlebitis on 38 patients who were treated in the Amarilis room of the Abiyasa Geriatric Pavilion of Prof. Dr. Margono Soekarjo Hospital. The study review was conducted on January 13 - 16, 2025. The instrument used to assess nurse compliance with infusion installation by using a standard SOP checklist for infusion installation. Observation of infusion installation was carried out when nurses performed infusion installation, then factors influencing the incidence of phlebitis were studied the size of the intravenous catheter used, the installation location and the length of infusion installation. The results of observations made in the Amarilis room found that SOP non-compliance was found, including not using a backing, not washing hands before action, not writing the date and time of insertion on the patient's infusion and not re-disinfecting the puncture area after being held to find the location of the vein. Based on observation data, the majority of respondents were compliant, namely 7 (70%) and non-compliant 3 (30%). Based on data taken from 38 patient medical records, it shows that 25 patients (66%) with intravenous catheters experienced phlebitis. External factors that can affect the incidence of phlebitis include: intravenous (IV) catheter size, length of catheter insertion, catheter insertion location which were also identified in this study. During the observation, it was also found that the incidence of phlebitis was not found even though the nurses did not comply with the SOP for infusion installation, this could be due to the fact that in carrying out infusion installation, the nurses performed aseptic techniques correctly, namely disinfecting the puncture area properly and correctly with an alcohol swab, and not holding it again after being disinfected. Based on the study conducted in the Amarilis room of Prof. Dr. Margono Soekarjo Hospital, it can be concluded that nurses' compliance with standard operating procedures (SOPs) in infusion insertion still needs to be improved. This study also indicates that although nurses have complied with SOPs, phlebitis can still occur due to external and internal factors that affect the patient's condition.